Writing the Nation - Berger, Stefan. author. aut Link
XII, 243 p.
Keywords: This book brings together experts on national history writing from all five continents to discuss the role of history in the making of national identities in a transnational and comparative way. The institutionalization and professionalisation of history writing is analysed in the context of history's increasing nationalization.